2014
DOI: 10.1016/j.vetimm.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum immunoglobulin G half-life in dairy calves fed colostrum, colostrum replacer or administered with intravenous bovine plasma

Abstract: In calves, passive immunity of immunoglobulins can be acquired through ingestion of colostrum or colostrum replacers. Plasma can been used to supplement immunoglobulins in healthy or sick calves. Serum half-life of colostral derived immuglobulin G (IgG) is estimated to be 20 days. Half-life of IgG is important in determining response to antigens and timing of vaccination in calves. To date studies evaluating half-life of colostrum replacer or plasma derived IgG are lacking. The objectives of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 15 publications
(22 reference statements)
4
27
2
Order By: Relevance
“…To the best of our knowledge, there are no studied reference values for serum IgG levels for calves 2-4 weeks old. For two day old calves, 10 mg/ml is commonly used as the minimum level for successful passive transfer, but earlier studies have shown that the amount of IgG in serum decreases slowly after birth, with a half-life of 28.5 days [33]. In the current study, 44.1% of the calves with low serum IgG (< 10 mg/ml on arrival; mean age 17 days) were treated at least once against BRD, compared with 34.2% of the calves with high serum IgG (> 10 mg/ml at arrival, mean age 17 days).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studied reference values for serum IgG levels for calves 2-4 weeks old. For two day old calves, 10 mg/ml is commonly used as the minimum level for successful passive transfer, but earlier studies have shown that the amount of IgG in serum decreases slowly after birth, with a half-life of 28.5 days [33]. In the current study, 44.1% of the calves with low serum IgG (< 10 mg/ml on arrival; mean age 17 days) were treated at least once against BRD, compared with 34.2% of the calves with high serum IgG (> 10 mg/ml at arrival, mean age 17 days).…”
Section: Discussionmentioning
confidence: 99%
“…Failure of passive immunity is a significant risk factor for morbidity and mortality from diseases of calves including diarrhea and pneumonia . In clinical settings, IV administration has been recommended as part of medical management of healthy or sick calves with FPI, that >24 h because colostral immunoglobulin G (IgG) absorption has ceased . A recent study evaluating serum IgG concentrations after IV plasma administration at the recommended dosage of 30 mL/kg indicated that the majority of calves did not achieve serum IgG concentrations consistent with adequate transfer of immunity (ie, serum IgG ≥1,000 mg/dL) at 48 h of age.…”
mentioning
confidence: 99%
“…In clinical settings, IV administration has been recommended as part of medical management of healthy or sick calves with FPI, that >24 h because colostral immunoglobulin G (IgG) absorption has ceased . A recent study evaluating serum IgG concentrations after IV plasma administration at the recommended dosage of 30 mL/kg indicated that the majority of calves did not achieve serum IgG concentrations consistent with adequate transfer of immunity (ie, serum IgG ≥1,000 mg/dL) at 48 h of age. A limitation of this study was that serum IgG concentrations were not evaluated until 48 h after plasma transfusion.…”
mentioning
confidence: 99%
See 2 more Smart Citations